Review of early and accurate detection of Parkinson’s disease - Mathew Biju, Soly; Al-Khatib, Obada; Chuan Lim, Hock; Malt, Suzanne; Zahid Sheikh, Hashir (Institute of Advanced Engineering and Science, 2024)
Parkinson’s disease (PD) is a central sensory system-based progressive illness with no cure. The origin of this illness is unknown. According to various research, it has been found that it is caused due to genetics or environmental factors. It is usually found in older people. However, there is no accurate treatment for this disease. So, the patient must be monitored periodically. It usually starts with deterioration in speech performance. The major problem with this disease is that it’s very costly to treat. The paper aims to report details of numerous aspects of detection of PD published in recent years based on the focus and benefits of the study, the methodology being used, accuracy of the system, and future research suggested for the study. A systematic study was done based on a search of the literature. A total of 50 articles were discovered.